Imperceptible non-blind watermarking and robustness against tone mapping operation attacks for high dynamic range images - Anbarjafari, Gholamreza; Ozcinar, Cagri (SPRINGER, 2018)
High dynamic range (HDR) imaging has experienced a widespread during the recent years through various technologies, including social network applications, which necessitates robust watermarking schemes to protect the copyright and image authentication. As watermarked high dynamic range images need to be tone mapped for visualization purposes on the traditional low dynamic range displays, the associated tone mapping operators (TMOs) can be deemed inevitable attacks. In this paper, we show that the state-of-the-art non-blind watermarking algorithms are vulnerable to the TMO's attacks. Based on the results of our investigation, we propose an improved non-blind watermarking method and extensively evaluate with state-of-the-art non-blind watermarking schemes using a broad set of TMOs' attacks. The proposed method first divides a given host image into patches, each of which is then decomposed using the discrete wavelet transform (DWT). The high-high sub-band of DWT is then passed through chirp-z transformation, followed by QR decomposition. The proposed solution embeds the watermark into each of value of the upper triangular matrix obtained from QR decomposition. The efficiency of the proposed embedding scheme is evaluated by applying 14 different TMOs on the watermarked image and extracting the embedded watermark. The average of 100 normalized correlation values for each image is then taken into account as a criterion for comparison, which demonstrates the noticeably stronger performance of the proposed watermarking scheme with respect to the state-of-the-art non-blind watermarking alternatives.
Keywords: DISCRETE WAVELET TRANSFORM; ENTROPY; MODEL